The Enforcement of the Payment of Lobolo and its Impact On Children’s Rights in South Africa - Ngema, Nqobizwe Mvelo (Potchefstroom Electronic Law Journal, 2017)
Various communities in South Africa practise the custom of lobolo (payment in kind or cash by a prospective husband or the head of his family to the head of the prospective wife’s family in consideration of a customary marriage). These communities may be divided into two groups, those practicing theleka (the withholding of a wife by her father or guardian from her husband to coerce him to pay the outstanding lobolo) and those that do not. In the communities practising theleka the amount of lobolo is not fixed and the father or guardian of the wife may from time to time theleka the wife and demand one to three head of cattle from his son-in-law. The wife and her children, if there are any, may be held by their maternal grandfather until the payment of lobolo has been met. The main issue this article examines is whether the custom of theleka impacts on the custody of children or not. It also examines the concept of the best interests of the child and finds that theleka custom in its current form does impact on the custody of the child and conflicts with the child’s best interests. The article suggests that theleka custom needs to be developed to conform to the Constitution. It also examines whether or not the custom of theleka constitutes abduction and family violence. The writer submits that it does not constitute abduction and family violence and advocates that theleka custom be allowed to continue.